2021
DOI: 10.1051/smdo/2021028
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of friction STIR welded AA6061 + SiCp metal matrix composite to increase joint tensile strength and reduce defects

Abstract: Friction stir welding has been used in automobiles, locomotive, and aircraft structures. This metal joining process exhibits defects like kissing bonds, micropores, and tunnels. Factors like the joining material, joint thickness, tool geometry, and operating parameters control the defects in friction stir welding. The parameters like tool rotation, tool pass speed, and tool force have a greater influence on the joint quality. In this study, these parameters are considered to augment the strength of the joint a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The spacing between these bands is equal to the distance that the tool covers while moving forward in every single rotation. Researchers reported that such macrostructures were formed due to the variation in grain size, particles and the precipitates distribution, crystallographic textures, dislocation density, and the chemistry due to the inter-mixing of the dissimilar alloys [15,[39][40][41][101][102][103][104][105][106][107][108]. Krishnan [109] during FSW of dissimilar AA6061-AA7075 alloys at different welding parameters reported that these variations were caused due to the frictional heat imparted to the material to heat and the forward movement of the rotating tool that extrudes the material about the RS that leads to the formation of the banded structure during the rotational motion of the FSW tool.…”
Section: Banded Structure Formation In Nzmentioning
confidence: 99%
“…The spacing between these bands is equal to the distance that the tool covers while moving forward in every single rotation. Researchers reported that such macrostructures were formed due to the variation in grain size, particles and the precipitates distribution, crystallographic textures, dislocation density, and the chemistry due to the inter-mixing of the dissimilar alloys [15,[39][40][41][101][102][103][104][105][106][107][108]. Krishnan [109] during FSW of dissimilar AA6061-AA7075 alloys at different welding parameters reported that these variations were caused due to the frictional heat imparted to the material to heat and the forward movement of the rotating tool that extrudes the material about the RS that leads to the formation of the banded structure during the rotational motion of the FSW tool.…”
Section: Banded Structure Formation In Nzmentioning
confidence: 99%
“…Quality control of welding is a crucial aspect of ensuring the reliability, safety, and durability of welded products [8]. Proper quality control measures help identify and rectify defects, prevent potential failures [9], and maintain consistent welding standards at whatever stages (figure 2) [8]. ML brough an innovative and efficient solution to overcome these problems.…”
Section: Introductionmentioning
confidence: 99%